Simulations of ELM-induced tungsten melt flow across misaligned plasma-facing components - L. Vignitchouk; S. Ratynskaia; The ASDEX Upgrade Team (Nuclear Fusion)
A computational fluid dynamics model of ELM-induced tungsten melt flow across a gap between misaligned plasma-facing components is validated against data from dedicated leading-edge exposures in the ASDEX Upgrade tokamak. The macroscopic behavior of the simulated flow in terms of stability and attachment to the underlying solid surface agrees with experimental observations and is consistent with simplified dimensionless criteria based on the balance between fluid inertia and surface tension. Quantitative predictions of the total mass deposited on the downstream side of the gap, along with the characteristic extent of such deposits, are also shown to match the empirical evidence. Furthermore, the accumulation of re-solidified material due to consecutive melt events is found to progressively smooth the gap edge, which promotes better overall flow attachment as well as the growth of overhangs whose dimensions can eventually exceed the gap width.